2013
DOI: 10.1016/j.idc.2013.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Liver and Kidney Transplantation in the Human Immunodeficiency Virus-Infected Patient

Abstract: HIV-infection is no longer an absolute contraindication for transplantation for patients with advanced kidney and liver failure. This article reviews the outcome data in the solid organ transplantation of HIV-infected patients that led to a change in thinking by the transplant community. We then review several emerging issues in the field such as eligibility criteria, selection of optimal immunosuppression agents and antiretroviral therapy in this population, and management of co-infection with Hepatitis B and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…Concerns surrounding opportunistic infections due to immunocompromise and reduced survival have been attenuated (1). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns surrounding opportunistic infections due to immunocompromise and reduced survival have been attenuated (1). …”
mentioning
confidence: 99%
“…Despite these additional complexities, multiple studies have demonstrated that graft and patient survivorship are comparable between HIV-infected and noninfected groups (3). HIV infection is, thus, no longer considered to be a contraindication to liver transplantation (1). …”
mentioning
confidence: 99%
“…Multiple evidence shows that immunosuppression in the context of SOT does not cause neither progression of HIV disease nor loss of viral suppression in patients taking ART . Our patient maintained an excellent immunovirologic control during the 15 months following transplantation.…”
Section: Discussionmentioning
confidence: 58%
“…A major concern about SOT in the HIV‐infected population is drug‐drug interactions. Antiretrovirals, especially protease inhibitors, are powerful cytochrome inhibitors that affect the metabolism of immunosuppressive drugs such as tacrolimus or cyclosporine making their adjustment quite challenging . Hence, inadequate exposure to immunosuppressive drugs with subtherapeutic serum levels may lead to graft rejection in the patient .…”
Section: Discussionmentioning
confidence: 99%
“…This was principally due to poor patient and graft survival as the immunosuppression required to prevent organ rejection frequently resulted in infectious complications as well as aggressive HCV recurrence [ 5 ]. Now, as well as improved survival in HIV-positive persons due to cART, recent advances in the treatment of hepatitis C with directly acting antiviral agents (DAAs) and prophylaxis of opportunistic infections mean that liver transplantation may be an increasingly viable option for co-infected patients with end-stage liver disease [ 6 ].…”
Section: Introductionmentioning
confidence: 99%